2020
DOI: 10.1186/s13011-019-0250-1
|View full text |Cite
|
Sign up to set email alerts
|

A rapid access to addiction medicine clinic facilitates treatment of substance use disorder and reduces substance use

Abstract: Background: Substance use is prevalent in Canada, yet treatment is inaccessible. The Rapid Access to Addiction Medicine (RAAM) clinic opened at the University Health Network (UHN) in January 2018 as part of a larger network of addictions clinics in Toronto, Ontario, to enable timely, low barrier access to medical treatment for substance use disorder (SUD). Patients attend on a walk-in basis without requiring an appointment or referral. We describe the RAAM clinic model, including referral patterns, patient dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…[32][33][34] Promising strategies include screening, brief intervention, treatment referrals, 35 managed alcohol programs 36 and case management. 37 Rapid access to addiction medicine clinics has been shown to reduce both substance use 38 and emergency department visits, 39 and may also have an impact on mortality in frequent users of emergency departments for alcohol-related mental and behavioural disorders. ‡Decreasing frequency with increasing ED use; not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Promising strategies include screening, brief intervention, treatment referrals, 35 managed alcohol programs 36 and case management. 37 Rapid access to addiction medicine clinics has been shown to reduce both substance use 38 and emergency department visits, 39 and may also have an impact on mortality in frequent users of emergency departments for alcohol-related mental and behavioural disorders. ‡Decreasing frequency with increasing ED use; not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary results of this trial led to the creation of the Mentoring, Education, and Clinical Tools for Addiction: Primary Care-Hospital Integration (META:PHI) project, a provincial initiative to spread this rapid access model of addiction care. Some of the clinics created following this initiative have demonstrated positive patient outcomes [25][26][27]. There are several ways that on-site and immediate access can be accomplished in addition to rapid access clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Having outpatient clinics available addresses concerns of initiating a chronic medication in an acute setting, titrating the dose, and providing ongoing care. Rapid access clinics demonstrate positive clinical outcomes and retention in care, forming a crucial component of ED-initiated treatment for OUD [ 9 , 29 ]. ED leadership should work closely with outpatient clinics to ensure rapid follow-up and a smooth transition of care from the ED to the outpatient clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Buprenorphine is increasingly accessible in Ontario after being included on the Ontario Drug Benefit formulary [ 6 ]. Buprenorphine induction in the ED has been shown to be a feasible and effective approach to begin medication for addiction treatment [ 7 9 ]. A randomized clinical trial found that ED-initiated buprenorphine significantly increased engagement in addiction treatment and decreased use of inpatient addiction services compared to referral or brief interventions in the ED [ 7 ].…”
Section: Introductionmentioning
confidence: 99%